Assessing the utility of eDNA as a tool to survey reef-fish communities in the Red Sea - DiBattista, J.; Coker, D.; Sinclair-Taylor, T.; Stat, M.; Berumen, M.; Bunce, Michael (Springer Verlag, 2017)
Relatively small volumes of water may contain sufficient environmental DNA (eDNA) to detect target aquatic organisms via genetic sequencing. We therefore assessed the utility of eDNA to document the diversity of coral reef fishes in the central Red Sea. DNA from seawater samples was extracted, amplified using fish-specific 16S mitochondrial DNA primers, and sequenced using a metabarcoding workflow. DNA sequences were assigned to taxa using available genetic repositories or custom genetic databases generated from reference fishes. Our approach revealed a diversity of conspicuous, cryptobenthic, and commercially relevant reef fish at the genus level, with select genera in the family Labridae over-represented. Our approach, however, failed to capture a significant fraction of the fish fauna known to inhabit the Red Sea, which we attribute to limited spatial sampling, amplification stochasticity, and an apparent lack of sequencing depth. Given an increase in fish species descriptions, completeness of taxonomic checklists, and improvement in species-level assignment with custom genetic databases as shown here, we suggest that the Red Sea region may be ideal for further testing of the eDNA approach.